Biomedical Waste and Solid Waste Management in the Time of COVID-19: A Comprehensive Review of the National and International Scenario and Guidelines - Capoor, Malini R.; Parida, Annapurna (Journal of Laboratory Physicians, 2021)
Biomedical waste generated during the diagnosis, isolation, and treatment of coronavirus disease 2019 (COVID-19) patients can also be the source of new infections; hence, it needs special consideration. Previous guidelines for the management of biomedical waste need to be revisited as the majority of COVID-19 patients remain asymptomatic and reside in community. Personal protective equipment (PPE) like masks, hazmat suits, gloves, and visors are now being used by the public also. Thus, the general household waste and disposables now make an exponential increase in the waste that can be considered an environmental hazard. In this article, the authors have tried to present the problems arising from COVID-19 waste and the recommendations put forth by competent authorities both nationally and internationally on COVID-19 waste management. Furthermore, in all the guidelines, it is crucial that the COVID-19 waste management follows environmentally sound principles and practices of biomedical waste management, with safe work and infection-control practices. Segregation of COVID-19 waste at source, awareness, and precautions at all steps of the waste-cycle are the only way ahead in this crisis.
Keywords: COVID-19 waste; biomedical waste; solid waste; guidelines